Hierarchically Textured Oleophobic Internal Coatings that Facilitate Drag Reduction of Viscous Oils in Macroscopic Laminar Flow. Issue 8 (2nd June 2020) - Cool, Nicholas; Douglas, Lacey; Gupta, Subodh; Banerjee, Sarbajit
Abstract : For transportation of hydrocarbon liquids via pipelines, reducing the frictional forces between internal walls and viscous oils through modification of the interfacial surface chemistry and topography represents a key imperative, enabling viscous oil flow at lower temperatures while mitigating the need for diluents. Although drag reduction of aqueous flows in lithographically patterned microchannels has been widely explored, herein drag reduction of oil flows within macroscopic tubing spanning several feet in length is demonstrated. Multiscale texturation is derived from the introduction of micron‐sized pits during electroless deposition of nickel and is augmented by nanoscale texturation derived from the incorporation of polytetrafluoroethylene (PTFE) beads within the coating. Further functionalization with a monolayer of 1 H, 1 H, 2 H, 2 H ‐perfluorooctanephosphonic acid yields a surface that is not wetted by water or viscous oils, yielding 17% drag reduction under laminar flow for castor oil and a slip length that approaches 329 μm. The results demonstrate a promising solution for obtaining robust plastronic architectures embedded within the inner walls of macroscopic tubing. The performance of such coatings is constrained primarily by the robustness of plastrons and molecular properties of the flow liquid with the latter modifying the solid/liquid interface energy as a result of surface adsorption. Abstract : Multiscale texturation from micron‐scale to nanoscale dimensions enables the generative design of surface texturation, which combined with self‐assembled monolayers, yields fundamental geometric and chemical descriptors for fluid flow. The interplay of chemical and topological characteristics resulting from stable plastrons, hierarchical texturation, and functionalization with a surface monolayer endows omniphobic character facilitating drag reduction by creating alternating slip/no‐slip regimes.